Sequence Characterization of DSG3 Gene to Know Its Role in High-Altitude Hypoxia Adaptation in the Chinese Cashmere Goat - Kumar, Chandar; Song, Shen; Jiang, Lin; He, Xiaohong; Zhao, Qianjun; Pu, Yabin; Malhi, Kanwar Kumar; Kamboh, Asghar Ali; Ma, Yuehui (Frontiers in Genetics, 2018)
The Tibetan cashmere goat is one of the main goat breeds used by people living in the plateau. It exhibits the distinct phenotypic characteristics observed in lowland goats, allowing them to adapt to the challenging conditions at high altitudes. It provides an ideal model for understanding the genetic mechanisms underlying high-altitude adaptation and hypoxia-related diseases. Our previous exome sequencing of five Chinese cashmere breeds revealed a candidate gene, DSG3 (Desmoglein 3), responsible for the high-altitude adaptation of the Tibetan goat. However, the whole DSG3 gene (44 kbp) consisting of 16 exons in the goat genome was not entirely covered by the exome sequencing. In this study, we resequenced all the 16 exons of the DSG3 gene in ten Chinese native goat populations. Twenty-seven SNP variants were found between the lowland and highland goat populations. The genetic distance (FST) of significant SNPs between the lowland and highland populations ranged from 0.42 to 0.58. By using correlation coefficient analysis, linkage disequilibrium, and haplotype network construction, we found three non-synonymous SNPs (R597E, T595I, and G572S) in exon 5 and two synonymous SNPs in exons 8 and 16 in DSG3. These mutations significantly segregated high- and low-altitude goats in two clusters, indicating the contribution of DSG3 to the high-altitude hypoxia adaptation in the Tibetan goat.